Pengaruh Lingkungan Sekolah Dan Minat Belajar Terhadap Prestasi Belajar Siswa Kelas IX SMP Negeri 6 Pematang Siantar Tahun Ajaran 2022/2023 - Lilis Sibarani; Anggun Tiur Ida Sinaga; Anton Luvi Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to gain knowledge about the influence of the school environment and interest in learning on the learning achievement of class IX students at SMP Negeri 6 Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was class IX students at SMP Negeri 6 Pematang Siantar with a total of 219 students. The research sample consisted of 142 students. The sampling technique used was simple random sampling technique. The data collection technique used was a questionnaire. The results of this research state that: 1) There is a positive influence of the school environment on learning achievement, this result can be seen in the t test where the t value of the school environment (1.175) < ttable (1.6559) which means this variable is not significant. 2) There is a positive and significant influence of interest in learning on learning achievement. This result can be seen in the t test where the calculated value of interest in learning (10.629) > t table (1.6559) which means this variable is significant. 3) The school environment and interest in learning together influence student learning achievement, this result can be seen in the F test where the Fcount value (74.632) > Ftable value (3.0612). The R Square coefficient of determination test was found to be 0.518, which means that 51.8% of school environment variables and interest in learning influence student learning achievement at SMP Negeri 6 Pematang Siantar school. Meanwhile, 48.2% is the influence of other variables not examined in this research.